Prevalence of Apparent Treatment-Resistant Hypertension in Chronic Kidney Disease in Two Large US Health Care Systems. Issue 10 (October 2022) - An, Jaejin; Kurella Tamura, Manjula; Odden, Michelle C.; Ni, Liang; Thomas, I-Chun; Montez-Rath, Maria E.; Sim, John J.
Visual Abstract: Abstract : Background and objectives: More intensive BP goals have been recommended for patients with CKD. We estimated the prevalence of apparent treatment-resistant hypertension among patients with CKD according to the 2017 American College of Cardiology/American Heart Association (ACC/AHA; BP goal <130/80 mm Hg) and 2021 Kidney Disease Improving Global Outcomes (KDIGO; systolic BP <120 mm Hg) guidelines in two US health care systems. Design, setting, participants, & measurements: We included adults with CKD (an eGFR <60 ml/min per 1.73 m 2 ) and treated hypertension from Kaiser Permanente Southern California and the Veterans Health Administration. Using electronic health records, we identified apparent treatment-resistant hypertension on the basis of ( 1 ) BP above the goal while prescribed three or more classes of antihypertensive medications or ( 2 ) prescribed four or more classes of antihypertensive medications regardless of BP. In a sensitivity analysis, we required diuretic use to be classified as apparent treatment-resistant hypertension. We estimated the prevalence of apparent treatment-resistant hypertension per clinical guideline and by CKD stage. Results: Among 44, 543 Kaiser Permanente Southern California and 241, 465 Veterans Health Administration patients with CKD and treated hypertension, the prevalence rates of apparent treatment-resistant hypertension were 39% (Kaiser Permanente Southern California) and 35% (Veterans Health Administration) per the 2017 ACC/AHA guideline and 48% (Kaiser Permanente Southern California) and 55% (Veterans Health Administration) per the 2021 KDIGO guideline. By requiring a diuretic as a criterion for apparent treatment-resistant hypertension, the prevalence rates of apparent treatment-resistant hypertension were lowered to 31% (Kaiser Permanente Southern California) and 23% (Veterans Health Administration) per the 2017 ACC/AHA guideline. The prevalence rates of apparent treatment-resistant hypertension were progressively higher at more advanced stages of CKD (34%/33%, 42%/36%, 52%/41%, and 60%/37% for Kaiser Permanente Southern California/Veterans Health Administration eGFR 45–59, 30–44, 15–29, and <15 ml/min per 1.73 m 2, respectively) per the 2017 ACC/AHA guideline. Conclusions: Depending on the CKD stage, up to a half of patients with CKD met apparent treatment-resistant hypertension criteria.